Association of the neutrophil percentage-to-albumin ratio after endovascular treatment and 3-month clinical outcomes - Cui, Chang; Liu, Liang; Chen, Hui-Sheng (Frontiers in Neurology, 2026)
Background and aimNeutrophil percentage-to-albumin ratio (NPAR) is associated with clinical outcomes in malignancy, cardiovascular disease, and stroke. This study aimed to evaluate whether NPAR levels are associated with clinical outcomes in patients with acute ischemic stroke (AIS) due to large vessel occlusion (LVO) who underwent endovascular treatment (EVT).MethodsFrom a prospective cohort, we consecutively enrolled patients with anterior circulation LVO-AIS who underwent EVT and had available admission and 48-h post-EVT NPAR data. Three-month clinical outcome was assessed using the modified Rankin Scale (mRS). Poor functional outcome was defined as functional dependence or death (mRS 3–6). Multivariable logistic regression analyses were performed to explore the relationship between NPAR levels and clinical outcomes.ResultsA total of 121 eligible patients were included in the final analysis. Multivariable logistic regression models showed that a higher 48-h NPAR level (Model 1: adjusted OR = 15.09, 95% CI 3.72–61.22, p < 0.001) and an increase in NPAR from admission to 48 h (Model 2: adjusted OR = 7.69, 95% CI 2.06–28.70, p = 0.002) were independently associated with poorer functional outcome. The optimal cutoff value of 48-h NPAR level for predicting poor functional outcome was 2.312, with a sensitivity of 66% and a specificity of 79%.ConclusionHigher 48-h follow-up NPAR levels and increases in NPAR from admission to 48 h were independent predictors of poor 3-month functional outcomes in patients with large vessel occlusion treated with endovascular therapy.Clinical trial registrationhttps://www.clinicaltrials.gov, identifier (NCT05092139).